Matthean Jesus and peacebuilding in Zimbabwe 2018–2019 - Chamburuka, Sheila W. (HTS teologiese studies, 2020)
This article is an assessment of the applicability of the Matthean Jesus’ ethics in the context of peacebuilding in Zimbabwe (2018–2019). The article explores the factors which led to the removal of former President Mugabe from the office, and the events which took place from 2018 to 2019. It is alleged that torture, brutality and political killings of people continue to resurface even during the leadership of the new President Emmerson Mnangagwa. Faced with the above challenges associated with violence, socio-political, economic and religious conflicts, civil unrest and polarisation of the Zimbabwean society, the article gives an analysis of the relevance and applicability of Jesus’ ethics as presented by Matthew in a bid to bring national healing, peace and reconciliation in Zimbabwe. The ethics of Jesus are meant to transform society for the better; therefore, the article also assesses the lessons which can be drawn from these ethics amid challenges posed by a lack of confession, truth telling and transformative justice in the face of gross political intimidation and torture in Zimbabwe. The article concludes that the Matthean Jesus ethics are applicable in the Zimbabwean context. However, the implementation of these ethics faces serious impediments, which need special attention, especially the need of all citizens, government, political leaders, church leaders and civil society leaders to join hands together with the National Peace and Reconciliation Commission in bringing national healing in Zimbabwe.Contribution: This article is part of the special collection ‘Africa Platform for NT Scholars’. It focuses on the assessment of the applicability of the Matthean Jesus’ ethics in the context of peacebuilding in Zimbabwe (2018–2019).The ethics of Jesus are meant to transform society for the better, therefore, it is within the scope of this theological journal that issues associated with violence, socio-political, economic and religious conflicts, civil unrest and polarization should be addressed, hence the article fits well within this scope.